Porous Cube‐Aggregated Co3O4 Microsphere‐Supported Gold Nanoparticles for Oxidation of Carbon Monoxide and Toluene. Issue 6 (5th June 2014) - Yang, Huanggen; Dai, Hongxing; Deng, Jiguang; Xie, Shaohua; Han, Wen; Tan, Wei; Jiang, Yang; Au, Chak Tong
Abstract Porous cube‐aggregated monodisperse Co3O4 microspheres and their supported gold (xAu/Co3O4 microsphere, x=1.6–7.4 wt %) nanoparticles (NPs) were fabricated using the glycerol‐assisted solvothermal and polyvinyl alcohol‐protected reduction methods. Physicochemical properties of the materials were characterized by means of numerous analytical techniques, and their catalytic activities were evaluated for the oxidation of toluene and CO. It is shown that the cubic Co3O4 microspheres were composed of aggregated cubes with a porous structure. The gold NPs with a size of 3.2–3.9 nm were uniformly deposited on the surface of Co3O4 microspheres. Among the Co3O4 microsphere and xAu/Co3O4 microsphere samples, the 7.4Au/Co3O4 microspheres performed the best, giving T90 % values (the temperature required for achieving a CO or toluene conversion of 90 % at a weight hourly space velocity of 20 000 mL g−1 h−1) of −8 and 250 °C for CO and toluene oxidation, respectively. In the case of 3.0 vol % water vapor introduction, a positive effect on CO oxidation and a small negative effect on toluene oxidation were observed over the 7.4Au/Co3O4 microsphere sample. The apparent activation energies obtained over the xAu/Co3O4 microsphere samples were in the ranges of 40.7–53.6 kJ mol−1 for toluene oxidation and 21.6–34.6 kJ mol−1 for CO oxidation. It is concluded that the higher oxygen adspecies concentration, better low‐temperature reducibility, and stronger interaction between gold NPs and Co3O4 as well as the porous microspherical structure were responsible for the excellent catalytic performance of 7.4Au/Co3O4 microsphere.